Large-Scale Sound and Precise Program Analysis. - Henglein, Fritz (Communications of the ACM, 2010)
An introduction is presented to the article "Reasoning About the Unknown in Static Analysis," by Isil Dillig, Thomas Dillig, and Alex Aiken.